Novel approaches and materials for healing asphalt cracks - Gedik, Abdulgazi; Ozcan, Ozgur; Ozcanan, Sedat (Croatian Soc Civil Engineers-Hsgi, 2023)
Premature cracks in an asphalt pavement may damage its intact structure, substantially decrease its load-bearing capacity, degrade its driving comfort and safety, and even lead to total pavement failure. This paper provides a detailed state-of-the-art review regarding the impact of new approaches and materials on the curing of asphalt cracking, along with an explanation of their advantages, deficiencies, improvement opportunities, and future perspectives. By providing this background information, this study intends to contribute to the discovery of ground-breaking technical solutions and cost-effective materials to remedy premature asphalt pavement cracks at the right place and time. Future studies are recommended to advance efforts to discover more effective, practical, cost-saving, sustainable, and eco-friendly methods and agents for healing asphalt cracks.
Keywords: self-healing; asphalt pavement; asphalt cracks; rejuvenator; heating